A foamed metal catalyst for producing methanol by hydrogenating carbon dioxide and a preparation method thereof

By hydrothermal etching on the surface of Cu foam, the supported ZnO-Al2O3/Cu foam catalyst is formed, which solves the problem of inactivating Cu/ZnO/Al2O3 catalyst in the prior art under high temperature conditions, and achieves a high activity, high selectivity and long-term stability of carbon dioxide hydrogenation to methanol catalyst.

CN117680149BActive Publication Date: 2025-04-11XIAMEN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311620808.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-28
Publication Date
2025-04-11
Estimated Expiration
2043-11-28

AI Technical Summary

Technical Problem

The Cu/ZnO/Al2O3 catalyst used in the prior art under high temperature conditions is prone to form Cu-CO species due to the combination of Cu particles and CO, resulting in the deactivation of the catalyst and the increase in the production of by-product CO, which affects the selectivity of methanol.

Method used

The oxide layer on the surface of Cu foam was removed by sonication treatment. The Cu foam surface was etched with oxalic acid and nitric acid solution under hydrothermal reaction to form a supported ZnO-Al2O3/Cu foam catalyst, which enhanced the effective specific surface area of ​​the catalyst and the dispersion of surface Cu.

Benefits of technology

The activity and selectivity of hydrogenation of carbon dioxide to produce methanol is significantly improved. The carbon dioxide conversion rate is greater than 23%, and the selectivity of methanol can reach more than 69%, and the long-term stability of the catalyst and the prospect of industrial application are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117680149B_ABST
    Figure CN117680149B_ABST
Patent Text Reader

Abstract

A foam metal catalyst for hydrogenating carbon dioxide to produce methanol and a preparation method thereof, comprising the following steps: 1) pre-treating Cu foam to remove the surface oxide layer; 2) mixing oxalic acid solution, zinc acetate dihydrate solution, and auxiliary metal nitrate solution, and then adding nitric acid and stirring; 3) hydrothermally reacting the treated Cu foam and the mixed solution, and then washing, drying, and roasting. The catalyst is suitable for the reaction of hydrogenating carbon dioxide to produce methanol, with carbon dioxide and hydrogen as reaction raw materials, carbon dioxide conversion rate exceeding 23%, and methanol selectivity as high as 69%. The preparation method is simple, and the hydrothermal etching method can make the active components more evenly dispersed and more firmly bonded to the substrate, and the good mass transfer and heat transfer performance enables it to transfer the heat released in the hydrogenation reaction in time, improve the methanol selectivity and extend the service life of the catalyst, and the catalyst does not need to be formed and has high mechanical strength, and has broad industrial application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of hydrogenation catalysis, and in particular to a foamed metal catalyst for preparing methanol by hydrogenating carbon dioxide and a preparation method thereof. Background Art

[0002] How to make CO 2 Resource utilization has become a hot topic in current research. 2 In the method, CO 2 Hydrogenation to produce methanol has attracted much attention. 1 It is an important transition intermediate for the transformation of resources into new materials and chemicals, and is widely used in the fields of alternative fuels, organic solvents, hydrogen storage carriers, etc. 2 Hydrogenation to methanol is a highly exothermic reaction, and the reaction temperature itself is relatively high, which can easily lead to overheating of the catalyst bed, causing the active components to agglomerate, and thus causing CO 2 The conversion rate dropped significantly. In addition, too high an ambient temperature would increase the amount of byproduct CO generated and reduce the methanol selectivity. 2 It also has a certain inertness, activating CO 2 It also needs to be completed under certain temperature conditions, so it is crucial to explore catalysts that can maintain good stability at higher reaction temperatures.

[0003] Thermal catalytic CO 2 Hydrogenation to methanol is currently the most promising large-scale industrial technology. At present, the reported Pd-based and Pt-based precious metal catalysts (Gotti A et al., J Catal., 1998, 175: 302-311) have good activity at low temperatures, but due to their high prices, they are far less than copper-based catalysts in industrial applications. The main method for industrial methanol synthesis is carbonyl synthesis (CO, CO 2 Pressure catalytic hydrogenation), Cu / ZnO / Al 2 O 3Heterogeneous catalysts are widely used in industrial production of methanol due to their advantages such as high methanol yield, good activity and low cost. The evaluation conditions are usually 200-300°C and 5-10MPa. Oxidation and sintering of Cu species under high temperature conditions have been identified as important mechanisms for the loss of activity of Cu-based catalysts, which seriously affect the activity and stability of the catalyst. Datye et al. (Datye AK et al., Catal. Today, 2006, 111: 59-67) studied the sintering particle size distribution under reducing and oxidizing conditions. The results showed that the size distribution of large particle Cu species can only come from particle migration and agglomeration, which lead to serious deactivation of the catalyst. Dominik et al. (Rasmussen DB et al., J. Catal., 2012, 293: 205-214) found that Cu / ZnO / Al, which is widely used in industrial methanol synthesis reactions, 2 O 3 Catalyst, because the reaction process under high temperature conditions will produce more CO, it is easier to cause Cu particles to combine with CO to form Cu-CO species, which can increase its migration on the ZnO surface and accelerate the Cu / ZnO / Al 2 O 3 Deactivation of the catalyst. Therefore, it is urgent to develop a carbon dioxide hydrogenation to methanol catalyst that can maintain high activity, high selectivity, and high stability under high temperature conditions. Summary of the invention

[0004] The purpose of the present invention is to solve the above problems in the prior art and to provide a foamed metal catalyst with high activity and high selectivity for producing methanol by hydrogenation of carbon dioxide and a preparation method thereof.

[0005] In order to achieve the above object, the present invention adopts the following technical scheme:

[0006] A method for preparing a foamed metal catalyst for preparing methanol by hydrogenating carbon dioxide comprises the following steps:

[0007] 1) Pretreatment of metal Cu foam: The Cu foam is placed in dilute hydrochloric acid for ultrasonic treatment to remove the surface oxide layer, and then cleaned and dried;

[0008] 2) mixing the oxalic acid solution, the zinc acetate dihydrate solution and the auxiliary metal nitrate solution, then adding nitric acid and stirring;

[0009] 3) hydrothermally reacting the metal Cu foam treated in step 1) with the mixed solution in step 2), and then washing, drying and calcining.

[0010] In step 1), specifically, the Cu foam sheet is cut into small pieces of (0.5-5)*(0.5-5) mm, 1-5 g of the Cu foam sheet is weighed and placed in 0.5-3 mol L-1 The surface oxide layer is removed by ultrasonic treatment in dilute hydrochloric acid for 5 to 30 minutes, wherein the molar ratio of Cu foam sheet to hydrochloric acid is 0.3 to 1, and the sheet is rinsed with 50 to 100 mL of distilled water for 5 to 10 times, and then dried in an oven at 30 to 50°C.

[0011] In step 2), the concentration of the oxalic acid solution is 0.5-3 mol / L, the concentration of the nitric acid is 6-8 mol / L, and the molar ratio of the Zn element to the nitric acid is 0.2-2.

[0012] In step 2), the stirring is performed at 30 to 60° C. for 2 to 12 hours.

[0013] In step 3), the temperature of the hydrothermal reaction is 120 to 170° C., and the hydrothermal time is 12 to 24 hours.

[0014] In step 3), the cleaning is performed by rinsing with 50 to 100 mL of distilled water for 5 to 10 times.

[0015] In step 3), the drying is carried out in an oven at 30 to 60° C. for 2 to 12 hours.

[0016] In step 3), the calcination is performed at 300-550° C. for 2-12 hours in an air atmosphere.

[0017] The catalyst composition is Cu foam, ZnO and other metal oxides MO x The metal element M is selected from at least one of Al, Zr, In, Ga, Ce, Mg, Ti, Y, Cr, La, and Mn. Based on the total mass of the catalyst, the mass fraction of ZnO is 30% to 50%, the mass fraction of other metal oxides is 5% to 20%, and the remainder is Cu foam.

[0018] The foamed metal catalyst is used for the reaction of hydrogenating carbon dioxide to produce methanol. The specific reaction conditions are: using a fixed bed reactor, the carbon dioxide hydrogenation reaction pressure is 10-100 bar, the reaction temperature is 180-320°C, H 2 With CO 2 The volume ratio is 1:9-9:1, and the reaction gas space velocity is 1000-50000 mL h -1 g -1 .

[0019] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:

[0020] 1. The catalyst of the present invention shows excellent activity and selectivity for selectively preparing methanol by hydrogenation of carbon dioxide, with a carbon dioxide conversion rate of more than 23% and a methanol selectivity of more than 69%;

[0021] 2. The present invention utilizes the chemical activity of Cu foam itself to endogenously grow on its skeleton surface to form a structural catalyst, and adds nitric acid during the hydrothermal etching process to enhance the etching of the Cu foam surface, so that more defect sites are exposed, which is convenient for auxiliary agent loading; by regulating the auxiliary agent components, content and element ratio, the effective specific surface area of ​​the catalyst and the dispersion of surface Cu are increased, and the conversion performance of the catalyst is significantly improved;

[0022] 3. The Cu foam of the present invention has good mass and heat transfer performance, and can timely dissipate the heat generated in the reaction process, avoiding the problem of catalyst deactivation caused by agglomeration of active components due to excessive temperature, thereby improving the long-term stability of the catalyst;

[0023] 4. The catalyst preparation process of the present invention is simple, does not require molding, has high mechanical strength, good repeatability, low industrial production cost, is easy to scale up production, and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 is the SEM image of the cleaned Cu foam;

[0025] Figure 2 This is a SEM image of the Cu foam after etching with oxalic acid + nitric acid provided in Comparative Example 1;

[0026] Figure 3 The ZnO-Al 2 O 3 SEM image of / Cu foam;

[0027] Figure 4 It is the stability performance diagram of the catalysts of Example 1 and Comparative Example 3. DETAILED DESCRIPTION

[0028] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention clearer and more understandable, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments.

[0029] Example 1

[0030] First, the Cu foam sheet was cut into small pieces of 1.5*1.5 mm. 2 g of Cu foam sheet was weighed and placed in 50 mL of 1 mol L -1Ultrasonic treatment in dilute hydrochloric acid for 20 minutes to remove the surface oxide layer, rinse with 100mL distilled water 5 times, and dry at 40℃; take 6.267g zinc acetate dihydrate and 5.016g aluminum nitrate nonahydrate and dissolve them in 30mL deionized water respectively, mix 20mL 1mol / L oxalic acid solution with zinc acetate dihydrate and aluminum nitrate nonahydrate solution, add 4.5mL 8mol / L nitric acid, and stir at 40℃ for 6h; place the treated Cu foam sheet and the mixed solution in a hydrothermal kettle for hydrothermal treatment, the hydrothermal temperature is 150℃, and the hydrothermal time is 24h. After cooling to room temperature, rinse the Cu foam sheet with 100mL distilled water, repeat 5 times; put the obtained Cu foam sheet in a 40℃ oven, dry for 6h, then put it in a muffle furnace and roast it at 400℃ for 4h in air atmosphere, and cool it naturally to room temperature to obtain ZnO-Al 2 O 3 / Cu foam metal catalyst.

[0031] The catalyst was used for the evaluation of carbon dioxide hydrogenation reaction. The specific operation was as follows: a fixed bed reactor was used, the catalyst loading amount was 1.0 g, and the reducing gas was 95% N by volume. 2 and 5% H 2 , gas flow rate was 100 mL / min, reduction was carried out at 230 °C and atmospheric pressure for 3 h. After the reduction was completed, CO was adjusted 2 The hydrogenation reaction pressure is 60 bar, the reaction temperature is 230 °C, and H 2 With CO 2 The volume ratio is 3:1, and the reaction gas space velocity is 6000mLh -1 g -1 The performance evaluation results of the catalyst are shown in Table 1.

[0032] Example 2

[0033] First, the Cu foam sheet was cut into small pieces of 1.5*1.5 mm. 2 g of Cu foam sheet was weighed and placed in 50 mL of 1 mol L -1Ultrasonic treatment in dilute hydrochloric acid for 20 minutes to remove the surface oxide layer, rinse with 100mL distilled water 5 times, and dry at 40℃; 6.267g zinc acetate dihydrate and 3.092g zirconium oxynitrate dihydrate were dissolved in 30mL deionized water respectively, 20mL oxalic acid solution with a concentration of 1mol / L was mixed with zinc acetate dihydrate and zirconium oxynitrate dihydrate solution, 4.5mL nitric acid with a concentration of 8mol / L was added, and stirred at 40℃ for 6h; the treated Cu foam sheet and the mixed solution were placed in a hydrothermal kettle for hydrothermal treatment, the hydrothermal temperature was 150℃, and the hydrothermal time was 24h. After cooling to room temperature, the Cu foam sheet was rinsed with 100mL distilled water, and repeated 5 times; the obtained Cu foam sheet was placed in a 40℃ oven, dried for 6h, and then placed in a muffle furnace and calcined at 400℃ for 4h in an air atmosphere, and naturally cooled to room temperature to obtain ZnO-ZrO 2 / Cu foam metal catalyst.

[0034] The catalyst was used for the evaluation of carbon dioxide hydrogenation reaction. The specific operation was as follows: a fixed bed reactor was used, the catalyst loading amount was 1.0 g, and the reducing gas was 95% N by volume. 2 and 5% H 2 The gas flow rate was 100 mL / min, and the reduction was carried out at 230 °C and normal pressure for 3 h. After the reduction was completed, the carbon dioxide hydrogenation reaction pressure was adjusted to 60 bar, the reaction temperature was 230 °C, and H 2 With CO 2 The volume ratio is 3:1, and the reaction gas space velocity is 6000mLh -1 g -1 The performance evaluation results of the catalyst are shown in Table 1.

[0035] Example 3

[0036] First, the Cu foam sheet was cut into small pieces of 1.5*1.5 mm. 2 g of Cu foam sheet was weighed and placed in 50 mL of 1 mol L -1 Ultrasonic treatment in dilute hydrochloric acid for 20 minutes to remove the surface oxide layer, rinse with 100mL distilled water 5 times, and dry at 40℃; take 6.267g zinc acetate dihydrate and 3.181g indium nitrate tetrahydrate and dissolve them in 30mL deionized water respectively, mix 20mL oxalic acid solution with zinc acetate dihydrate and indium nitrate tetrahydrate solution with a concentration of 1mol / L, add 4.5mL nitric acid with a concentration of 8mol / L, and stir at 40℃ for 6h; place the treated Cu foam sheet and the mixed solution in a hydrothermal kettle for hydrothermal treatment, the hydrothermal temperature is 150℃, and the hydrothermal time is 24h. After cooling to room temperature, rinse the Cu foam sheet with 100mL distilled water, repeat 5 times; put the obtained Cu foam sheet in a 40℃ oven, dry for 6h, then put it in a muffle furnace and roast it at 400℃ for 4h in an air atmosphere, and cool it naturally to room temperature to obtain ZnO-In2 O 3 / Cu foam metal catalyst.

[0037] The catalyst was used for the evaluation of carbon dioxide hydrogenation reaction. The specific operation was as follows: a fixed bed reactor was used, the catalyst loading amount was 1.0 g, and the reducing gas was 95% N by volume. 2 and 5% H 2 , gas flow rate was 100 mL / min, reduction was carried out at 230 °C and atmospheric pressure for 3 h. After the reduction was completed, CO was adjusted 2 The hydrogenation reaction pressure is 60 bar, the reaction temperature is 230 °C, and H 2 With CO 2 The volume ratio is 3:1, and the reaction gas space velocity is 6000mLh -1 g -1 The performance evaluation results of the catalyst are shown in Table 1.

[0038] Example 4

[0039] First, the Cu foam sheet was cut into small pieces of 1.5*1.5 mm. 2 g of Cu foam sheet was weighed and placed in 50 mL of 1 mol L -1 Ultrasonic treatment in dilute hydrochloric acid for 20 minutes to remove the surface oxide layer, rinse with 100mL distilled water 5 times, and dry at 40℃; take 6.267g zinc acetate dihydrate and 2.194g gallium nitrate nine hydrate and dissolve them in 30mL deionized water respectively, mix 20mL oxalic acid solution with zinc acetate dihydrate and gallium nitrate nine hydrate solution with a concentration of 1mol / L, add 4.5mL nitric acid with a concentration of 8mol / L, and stir at 40℃ for 6h; place the treated Cu foam sheet and the mixed solution in a hydrothermal kettle for hydrothermal treatment, the hydrothermal temperature is 150℃, and the hydrothermal time is 24h. After cooling to room temperature, rinse the Cu foam sheet with 100mL distilled water, repeat 5 times; put the obtained Cu foam sheet in a 40℃ oven, dry for 6h, then put it in a muffle furnace and roast it at 400℃ for 4h in air atmosphere, and cool it naturally to room temperature to obtain ZnO-Ga 2 O 3 / Cu foam metal catalyst.

[0040] The catalyst was used for the evaluation of carbon dioxide hydrogenation reaction. The specific operation was as follows: a fixed bed reactor was used, the catalyst loading amount was 1.0 g, and the reducing gas was 95% N by volume. 2 and 5% H 2 , gas flow rate was 100 mL / min, reduction was carried out at 230 °C and atmospheric pressure for 3 h. After the reduction was completed, CO was adjusted 2 The hydrogenation reaction pressure is 60 bar, the reaction temperature is 230 °C, and H 2 With CO 2 The volume ratio is 3:1, and the reaction gas space velocity is 6000mLh-1 g -1 The performance evaluation results of the catalyst are shown in Table 1.

[0041] Example 5

[0042] First, the Cu foam sheet was cut into small pieces of 1.5*1.5 mm. 2 g of Cu foam sheet was weighed and placed in 50 mL of 1 mol L -1 Ultrasonic treatment in dilute hydrochloric acid for 20 minutes to remove the surface oxide layer, rinse with 100mL distilled water 5 times, and dry at 40℃; 6.267g zinc acetate dihydrate and 2.194g cerium nitrate hexahydrate were dissolved in 30mL deionized water respectively, 20mL oxalic acid solution with a concentration of 1mol / L was mixed with zinc acetate dihydrate and cerium nitrate hexahydrate solution, 4.5mL nitric acid with a concentration of 8mol / L was added, and stirred at 40℃ for 6h; the treated Cu foam sheet and the mixed solution were placed in a hydrothermal kettle for hydrothermal treatment, the hydrothermal temperature was 150℃, and the hydrothermal time was 24h. After cooling to room temperature, the Cu foam sheet was rinsed with 100mL distilled water, and repeated 5 times; the obtained Cu foam sheet was placed in a 40℃ oven, dried for 6h, and then placed in a muffle furnace and calcined at 400℃ for 4h in an air atmosphere, and naturally cooled to room temperature to obtain ZnO-CeO 2 / Cu foam metal catalyst.

[0043] The catalyst was used for the evaluation of carbon dioxide hydrogenation reaction. The specific operation was as follows: a fixed bed reactor was used, the catalyst loading amount was 1.0 g, and the reducing gas was 95% N by volume. 2 and 5% H 2 , gas flow rate was 100 mL / min, reduction was carried out at 230 °C and atmospheric pressure for 3 h. After the reduction was completed, CO was adjusted 2 The hydrogenation reaction pressure is 60 bar, the reaction temperature is 230 °C, and H 2 With CO 2 The volume ratio is 3:1, and the reaction gas space velocity is 6000mLh -1 g -1 The performance evaluation results of the catalyst are shown in Table 1.

[0044] Example 6

[0045] First, the Cu foam sheet was cut into small pieces of 1.5*1.5 mm. 2 g of Cu foam sheet was weighed and placed in 50 mL of 1 mol L -1Ultrasonic treatment in dilute hydrochloric acid for 20 minutes to remove the surface oxide layer, rinse with 100mL distilled water 5 times, and dry at 40℃; 6.267g zinc acetate dihydrate and 3.428g magnesium nitrate hexahydrate were dissolved in 30mL deionized water respectively, 20mL oxalic acid solution with a concentration of 1mol / L was mixed with zinc acetate dihydrate and magnesium nitrate hexahydrate solution, 4.5mL nitric acid with a concentration of 8mol / L was added, and stirred at 40℃ for 6h; the treated Cu foam sheet and the mixed solution were placed in a hydrothermal kettle for hydrothermal treatment, the hydrothermal temperature was 150℃, and the hydrothermal time was 24h. After cooling to room temperature, the Cu foam sheet was rinsed with 100mL distilled water, and repeated 5 times; the obtained Cu foam sheet was placed in a 40℃ oven, dried for 6h, and then placed in a muffle furnace and calcined at 400℃ for 4h in an air atmosphere, and naturally cooled to room temperature to obtain ZnO-MgO / Cu foam metal catalyst.

[0046] The catalyst was used for the evaluation of carbon dioxide hydrogenation reaction. The specific operation was as follows: a fixed bed reactor was used, the catalyst loading amount was 1.0 g, and the reducing gas was 95% N by volume. 2 and 5% H 2 , gas flow rate was 100 mL / min, reduction was carried out at 230 °C and atmospheric pressure for 3 h. After the reduction was completed, CO was adjusted 2 The hydrogenation reaction pressure is 60 bar, the reaction temperature is 230 °C, and H 2 With CO 2 The volume ratio is 3:1, and the reaction gas space velocity is 6000mLh -1 g -1 The performance evaluation results of the catalyst are shown in Table 1.

[0047] Example 7

[0048] First, the Cu foam sheet was cut into small pieces of 1.5*1.5 mm. 2 g of Cu foam sheet was weighed and placed in 50 mL of 1 mol L -1 Ultrasonic treatment in dilute hydrochloric acid for 20 minutes to remove the surface oxide layer, rinse with 100mL distilled water 5 times, and dry at 40℃; 6.267g zinc acetate dihydrate and 4.551g tetrabutyl titanate were dissolved in 30mL deionized water respectively, 20mL oxalic acid solution with a concentration of 1mol / L was mixed with zinc acetate dihydrate and tetrabutyl titanate solution, 4.5mL nitric acid with a concentration of 8mol / L was added, and stirred at 40℃ for 6h; the treated Cu foam sheet and the mixed solution were placed in a hydrothermal kettle for hydrothermal treatment, the hydrothermal temperature was 150℃, and the hydrothermal time was 24h. After cooling to room temperature, the Cu foam sheet was rinsed with 100mL distilled water, and repeated 5 times; the obtained Cu foam sheet was placed in a 40℃ oven, dried for 6h, and then placed in a muffle furnace and calcined at 400℃ for 4h in an air atmosphere, and naturally cooled to room temperature to obtain ZnO-TiO 2 / Cu foam metal catalyst.

[0049] The catalyst was used for the evaluation of carbon dioxide hydrogenation reaction. The specific operation was as follows: a fixed bed reactor was used, the catalyst loading amount was 1.0 g, and the reducing gas was 95% N by volume. 2 and 5% H 2 , gas flow rate was 100 mL / min, reduction was carried out at 230 °C and atmospheric pressure for 3 h. After the reduction was completed, CO was adjusted 2 The hydrogenation reaction pressure is 60 bar, the reaction temperature is 230 °C, and H 2 With CO 2 The volume ratio is 3:1, and the reaction gas space velocity is 6000mLh -1 g -1 The performance evaluation results of the catalyst are shown in Table 1.

[0050] Example 8

[0051] First, the Cu foam sheet was cut into small pieces of 1.5*1.5 mm. 2 g of Cu foam sheet was weighed and placed in 50 mL of 1 mol L -1 Ultrasonic treatment in dilute hydrochloric acid for 20 minutes to remove the surface oxide layer, rinse with 100mL distilled water 5 times, and dry at 40℃; take 6.267g zinc acetate dihydrate and 4.997g yttrium nitrate hexahydrate and dissolve them in 30mL deionized water respectively, mix 20mL oxalic acid solution with zinc acetate dihydrate and yttrium nitrate hexahydrate, add 4.5mL nitric acid with a concentration of 8mol / L, and stir at 40℃ for 6h; place the treated Cu foam sheet and the mixed solution in a hydrothermal kettle for hydrothermal treatment, the hydrothermal temperature is 150℃, and the hydrothermal time is 24h. After cooling to room temperature, rinse the Cu foam sheet with 100mL distilled water, repeat 5 times; put the obtained Cu foam sheet in a 40℃ oven, dry for 6h, then put it in a muffle furnace and roast it at 400℃ for 4h in air atmosphere, and cool it naturally to room temperature to obtain ZnO-Y 2 O 3 / Cu foam metal catalyst.

[0052] The catalyst was used for the evaluation of carbon dioxide hydrogenation reaction. The specific operation was as follows: a fixed bed reactor was used, the catalyst loading amount was 1.0 g, and the reducing gas was 95% N by volume. 2 and 5% H 2 , gas flow rate was 100 mL / min, reduction was carried out at 230 °C and atmospheric pressure for 3 h. After the reduction was completed, CO was adjusted 2 The hydrogenation reaction pressure is 60 bar, the reaction temperature is 230 °C, and H 2 With CO 2 The volume ratio is 3:1, and the reaction gas space velocity is 6000mLh -1 g -1The performance evaluation results of the catalyst are shown in Table 1.

[0053] Example 9

[0054] First, the Cu foam sheet was cut into small pieces of 1.5*1.5 mm. 2 g of Cu foam sheet was weighed and placed in 50 mL of 1 mol L -1 Ultrasonic treatment in dilute hydrochloric acid for 20 minutes to remove the surface oxide layer, rinse with 100mL distilled water 5 times, and dry at 40℃; take 6.267g zinc acetate dihydrate and 3.182g chromium nitrate nine hydrate and dissolve them in 30mL deionized water respectively, mix 20mL oxalic acid solution with zinc acetate dihydrate and chromium nitrate nine hydrate solution with a concentration of 1mol / L, add 4.5mL nitric acid with a concentration of 8mol / L, and stir at 40℃ for 6h; place the treated Cu foam sheet and the mixed solution in a hydrothermal kettle for hydrothermal treatment, the hydrothermal temperature is 150℃, and the hydrothermal time is 24h. After cooling to room temperature, rinse the Cu foam sheet with 100mL distilled water, repeat 5 times; put the obtained Cu foam sheet in a 40℃ oven, dry for 6h, then put it in a muffle furnace and roast it at 400℃ for 4h in air atmosphere, and cool it naturally to room temperature to obtain ZnO-Cr 2 O 3 / Cu foam metal catalyst.

[0055] The catalyst was used for the evaluation of carbon dioxide hydrogenation reaction. The specific operation was as follows: a fixed bed reactor was used, the catalyst loading amount was 1.0 g, and the reducing gas was 95% N by volume. 2 and 5% H 2 , gas flow rate was 100 mL / min, reduction was carried out at 230 °C and atmospheric pressure for 3 h. After the reduction was completed, CO was adjusted 2 The hydrogenation reaction pressure is 60 bar, the reaction temperature is 230 °C, and H 2 With CO 2 The volume ratio is 3:1, and the reaction gas space velocity is 6000mLh -1 g -1 The performance evaluation results of the catalyst are shown in Table 1.

[0056] Example 10

[0057] First, the Cu foam sheet was cut into small pieces of 1.5*1.5 mm. 2 g of Cu foam sheet was weighed and placed in 50 mL of 1 mol L -1Ultrasonic treatment in dilute hydrochloric acid for 20 minutes to remove the surface oxide layer, rinse with 100mL distilled water 5 times, and dry at 40℃; take 6.267g zinc acetate dihydrate and 2.791g lanthanum nitrate hexahydrate and dissolve them in 30mL deionized water respectively, mix 20mL 1mol / L oxalic acid solution with zinc acetate dihydrate and lanthanum nitrate hexahydrate solution, add 4.5mL 8mol / L nitric acid, and stir at 40℃ for 6h; place the treated Cu foam sheet and the mixed solution in a hydrothermal kettle for hydrothermal treatment, the hydrothermal temperature is 150℃, and the hydrothermal time is 24h. After cooling to room temperature, rinse the Cu foam sheet with 100mL distilled water, repeat 5 times; put the obtained Cu foam sheet in a 40℃ oven, dry for 6h, then put it in a muffle furnace and roast it at 400℃ for 4h in air atmosphere, and cool it naturally to room temperature to obtain ZnO-La 2 O 3 / Cu foam metal catalyst.

[0058] The catalyst was used for the evaluation of carbon dioxide hydrogenation reaction. The specific operation was as follows: a fixed bed reactor was used, the catalyst loading amount was 1.0 g, and the reducing gas was 95% N by volume. 2 and 5% H 2 , gas flow rate was 100 mL / min, reduction was carried out at 230 °C and atmospheric pressure for 3 h. After the reduction was completed, CO was adjusted 2 The hydrogenation reaction pressure is 60 bar, the reaction temperature is 230 °C, and H 2 With CO 2 The volume ratio is 3:1, and the reaction gas space velocity is 6000mLh -1 g -1 The performance evaluation results of the catalyst are shown in Table 1.

[0059] Embodiment 11

[0060] First, the Cu foam sheet was cut into small pieces of 1.5*1.5 mm. 2 g of Cu foam sheet was weighed and placed in 50 mL of 1 mol L -1Ultrasonic treatment in dilute hydrochloric acid for 20 minutes to remove the surface oxide layer, rinse with 100mL distilled water 5 times, and dry at 40℃; 6.267g zinc acetate dihydrate and 3.356g manganese nitrate tetrahydrate were dissolved in 30mL deionized water respectively, 20mL oxalic acid solution with a concentration of 1mol / L was mixed with zinc acetate dihydrate and manganese nitrate tetrahydrate solution, 4.5mL nitric acid with a concentration of 8mol / L was added, and stirred at 40℃ for 6h; the treated Cu foam sheet and the mixed solution were placed in a hydrothermal kettle for hydrothermal treatment, the hydrothermal temperature was 150℃, and the hydrothermal time was 24h. After cooling to room temperature, the Cu foam sheet was rinsed with 100mL distilled water, and repeated 5 times; the obtained Cu foam sheet was placed in a 40℃ oven, dried for 6h, and then placed in a muffle furnace and calcined at 400℃ for 4h in an air atmosphere, and naturally cooled to room temperature to obtain ZnO-MnO 2 / Cu foam metal catalyst.

[0061] The catalyst was used for the evaluation of carbon dioxide hydrogenation reaction. The specific operation was as follows: a fixed bed reactor was used, the catalyst loading amount was 1.0 g, and the reducing gas was 95% N by volume. 2 and 5% H 2 , gas flow rate was 100 mL / min, reduction was carried out at 230 °C and atmospheric pressure for 3 h. After the reduction was completed, CO was adjusted 2 The hydrogenation reaction pressure is 60 bar, the reaction temperature is 230 °C, and H 2 With CO 2 The volume ratio is 3:1, and the reaction gas space velocity is 6000mLh -1 g -1 The performance evaluation results of the catalyst are shown in Table 1.

[0062] Comparative Example 1

[0063] The catalyst preparation method is the same as that in Example 1, except that ZnO and other metal oxides are not added during the preparation process, and a Cu foam metal catalyst is obtained after being etched simultaneously with oxalic acid and nitric acid.

[0064] The catalyst was used for the evaluation of carbon dioxide hydrogenation reaction. The specific operation was as follows: a fixed bed reactor was used, the catalyst loading amount was 1.0 g, and the reducing gas was 95% N by volume. 2 and 5% H 2 , gas flow rate was 100 mL / min, reduction was carried out at 230 °C and atmospheric pressure for 3 h. After the reduction was completed, CO was adjusted 2 The hydrogenation reaction pressure is 60 bar, the reaction temperature is 230 °C, and H 2 With CO 2 The volume ratio is 3:1, and the reaction gas space velocity is 6000mLh -1 g -1 The performance evaluation results of the catalyst are shown in Table 1.

[0065] Comparative Example 2

[0066] The catalyst preparation method is the same as that in Example 1, except that only ZnO is added without other metal oxides to obtain a ZnO / Cu foamed metal catalyst.

[0067] The catalyst was used for the evaluation of carbon dioxide hydrogenation reaction. The specific operation was as follows: a fixed bed reactor was used, the catalyst loading amount was 1.0 g, and the reducing gas was 95% N by volume. 2 and 5% H 2 , gas flow rate was 100 mL / min, reduction was carried out at 230 °C and atmospheric pressure for 3 h. After the reduction was completed, CO was adjusted 2 The hydrogenation reaction pressure is 60 bar, the reaction temperature is 230 °C, and H 2 With CO 2 The volume ratio is 3:1, and the reaction gas space velocity is 6000mLh -1 g -1 The performance evaluation results of the catalyst are shown in Table 1.

[0068] Comparative Example 3

[0069] The commercial copper-zinc-aluminum catalyst of Shanghai Zhuoran Co., Ltd. was used to compare the commercial catalyst with the self-made ZnO-Al 2 O 3 / Cu foam performance comparison.

[0070] The catalyst was used for the evaluation of carbon dioxide hydrogenation reaction. The specific operation was as follows: a fixed bed reactor was used, the catalyst loading amount was 1.0 g, and the reducing gas was 95% N by volume. 2 and 5% H 2 , gas flow rate was 100 mL / min, reduction was carried out at 230 °C and atmospheric pressure for 3 h. After the reduction was completed, CO was adjusted 2 The hydrogenation reaction pressure is 60 bar, the reaction temperature is 230 °C, and H 2 With CO 2 The volume ratio is 3:1, and the reaction gas space velocity is 6000mLh -1 g -1 The performance evaluation results of the catalyst are shown in Table 1.

[0071] Depend on Figures 1 to 3 The porous skeleton structure of Cu foam can be seen. After etching, a large number of active clusters grow in situ on the Cu foam skeleton with layer-by-layer stacking morphology.

[0072] Figure 4 The diagram shows the stability performance of the catalysts of Example 1 and Comparative Example 3. It can be seen that the catalysts prepared by the present invention have good stability.

[0073] As can be seen from the following Table 1, the catalyst of the present invention is suitable for the reaction of hydrogenating carbon dioxide to produce methanol. With carbon dioxide and hydrogen as reaction raw materials, the carbon dioxide conversion rate can reach 23% and the methanol selectivity can reach 69%.

[0074] Table 1

[0075]

[0076] Note: The above catalytic performances are all evaluation results when the reaction time is 20h.

[0077] Table 2

[0078] sample <![CDATA[S BET (m 2 g -1 )]]> <![CDATA[V total (cm 3 g -1 )]]> <![CDATA[D BJH (nm) <!-- 7 -->]]> Comparative Example 1 27.7 0.034 18.1 Comparative Example 2 33.1 0.049 8.7 Example 1 59.3 0.058 7.3

[0079] Table 2 shows the BET specific surface area test results of different samples. It can be seen from the table that after loading metal, the specific surface area of ​​the sample increases.

[0080] The catalyst of the present invention uses Cu foam with excellent mass transfer and heat transfer performance as a support carrier, and after pretreatment to remove the oxide layer on the surface of the Cu foam, a large number of defect sites are etched on the surface of the Cu foam by a mixed solution of oxalic acid and nitric acid under hydrothermal conditions, and the etched Cu particles react with the added ZnO and other auxiliary components to obtain a supported foam metal catalyst. The catalyst has excellent performance and a simple preparation method. The hydrothermal etching method can make the active components more evenly dispersed and more firmly combined with the substrate. The good mass transfer and heat transfer performance enables it to transfer the heat released in the hydrogenation reaction in time, improve the methanol selectivity and also extend the service life of the catalyst. The catalyst does not need to be formed and has high mechanical strength, and has broad industrial application prospects.

Claims

1. A method for preparing a foamed metal catalyst for hydrogenating carbon dioxide to methanol, characterized in that: The following steps are involved: 1) Pretreatment of metal Cu foam: The Cu foam is placed in dilute hydrochloric acid for ultrasonic treatment to remove the surface oxide layer, and then cleaned and dried; 2) mixing oxalic acid solution, zinc acetate dihydrate solution and auxiliary metal nitrate solution, then adding nitric acid and stirring; wherein the auxiliary metal element M is selected from at least one of Al, Zr, In, Ga, Ce, Mg, Ti, Y, Cr, La and Mn; 3) hydrothermally reacting the metal Cu foam treated in step 1) with the mixed solution in step 2), and then washing, drying and calcining.

2. The method for preparing a foamed metal catalyst for preparing methanol by hydrogenation of carbon dioxide according to claim 1, characterized in that: In step 1), the concentration of the dilute hydrochloric acid is 0.5-3 mol L -1 .

3. The method for preparing a foamed metal catalyst for preparing methanol by hydrogenation of carbon dioxide as claimed in claim 1, characterized in that: In step 2), the concentration of the oxalic acid solution is 0.5-3 mol / L, the concentration of the nitric acid is 6-8 mol / L, and the molar ratio of the Zn element to the nitric acid is 0.2-2.

4. The method for preparing a foamed metal catalyst for preparing methanol by hydrogenation of carbon dioxide as claimed in claim 1, characterized in that: In step 2), the stirring is performed at 30-60° C. for 2-12 hours.

5. The method for preparing a foamed metal catalyst for preparing methanol by hydrogenation of carbon dioxide as claimed in claim 1, characterized in that: In step 3), the temperature of the hydrothermal reaction is 120-170° C., and the hydrothermal time is 12-24 h.

6. The method for preparing a foamed metal catalyst for preparing methanol by hydrogenation of carbon dioxide according to claim 1, characterized in that: In step 3), the calcination is carried out at 300-550° C. for 2-12 h in an air atmosphere.

7. The foamed metal catalyst prepared by the preparation method according to any one of claims 1 to 6, characterized in that: The catalyst composition is Cu foam, ZnO and other metal oxides MO x The metal element M is selected from at least one of Al, Zr, In, Ga, Ce, Mg, Ti, Y, Cr, La, and Mn. Based on the total mass of the catalyst, the mass fraction of ZnO is 30% to 50%, the mass fraction of other metal oxides is 5% to 20%, and the remainder is Cu foam.

8. The use of the foamed metal catalyst according to claim 7, characterized in that: Used in the reaction of carbon dioxide hydrogenation to produce methanol.

9. The use according to claim 8, characterized in that: The fixed bed reactor is used, the carbon dioxide hydrogenation reaction pressure is 10-100 bar, the reaction temperature is 180-320 °C, the volume ratio of H2 to CO2 is 1:9-9:1, and the reaction gas space velocity is 1000-50000 mL h -1 g -1 .

Citation Information

Patent Citations

  • Preparation method of CuO / Cu2O / ZnO heterojunction photoelectric catalytic material

    CN113019380A

  • Preparation method and application of super-hydrophobic transition metal material / foam iron-nickel alloy structured catalyst

    CN113578325A